Artemisia argyi Leveil. et Vaniot (Asteraceae) в Києві та Криму: біологічні особливості, інтродукція, хімічний склад, можливості використання - Bagatska, T.S.; Logvinenko, L.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2012)
The results of using alien plant – Artemisia argyi Leveil. et Vaniot in Kyiv and its introduction in Crimea are represented. Artemisia argyi botanical description is given. Chemical composition of essential oil on basis of chromatographic analysis is established. The potentialies of plant using are determine.